(untitled) (Kronika Bydgoska, 2014)
“Solidarity” was a social movement for democratization and deep reforms of the political system, which took a form of a trade union under the name: Independent Self-governing Trade Union “Solidarity.” It was active in communities of state employees, individual farmers and crafts. The history of NSZZ “Solidarity” in the Bydgoszcz region was a topic of historical study. The source of all of the mentioned works was the private collection of Solidarity related documents and newspapers, and in particular archives from the collection of the Archive of the Institute of National Remembrance in Bydgoszcz. The authors usually did not reach for sources collected in the State Archive of Bydgoszcz. The purpose of the article was to present the mentioned materials. The first group consists of records of Trade Union units, usually company committees operating in workplaces and institutions. The second, biggest group includes archives and newspapers related to NSZZ “Solidarity,” coming from private collections donated to the State Archive of Bydgoszcz. The third part of the archives related to the Solidarity movement comprises primarily Parliament records, i.e. documents for elections to the Sejm and Senate, elections for the President of Poland and elections for local government. A separate group of documents are records of the Regional Committee of the Polish United Workers’ Party in Bydgoszcz.